Aligning University Vision–Mission using COBIT 2019 Goals Cascade - Palar, Syalomita; Sentinuwo, Steven Ray; Rumagit, Arthur (Universitas Sam Ratulangi, 2026)
Abstract — A university's strategic objectives need to be systematically aligned with InformationTechnology (IT) governance to ensure IT truly supports the achievement of the institution's vision and mission. An effective method to achieve this goal is by using the COBIT 2019 framework. The approach taken is a two-stage mapping process. The first stage involves translating the university's Vision and Mission into COBIT's Enterprise Goals (EG). Then, in the second stage, each EG is mapped to the relevant IT Alignment Goals (AG). This step-by-step mapping process serves as a bridge connecting the university's high-level strategic direction with specific IT management activities and objectives. The result of this method is the creation of a clear and measurable connection between the university's strategic objectives and the main focus areas of IT governance, namely Value, Risk, and Performance. This connection shows how each university objective is influenced or supported by IT governance efforts. The implications are significant, as the mapping results become a strong foundation for developing the university's IT roadmap. Additionally, it helps the institution prioritize which COBIT management and governance domains should be optimized first to align with the institution's most pressing strategic needs. Thus, IT transforms from merely a supporting function into a strategic driver for the university. Key words — COBIT 2019; Enterprise Goals; Alignment Goals; IT Governance; Higher EducationStrategy; Strategic Mapping.